Naphtyl-imidazo-anthraquinones as novel colorimetric and fluorimetric chemosensors for ion sensing - Batista, Rosa M. F. (2013)
Novel colorimetric and fluorimetric chemosensors for F− and CN− containing anthraquinone and imidazole as signalling/binding sites have been synthesised and characterised. Upon addition of F−, CN− and OH− to acetonitrile solutions of compounds 1-2, a marked colour change from yellow to pink was observed and the fluorescence emission of 1 was switched “on”, whereas for 2 there was a fluorescence quenching. Considering recognition in organic aqueous mixture, it was found that selectivity for CN- was achieved for both receptors, with an easily detectable colour change from yellow to orange. Compounds 1-2 in their deprotonated form, after fluoride addition, were studied as metal ion chemosensors and displayed a drastic change from pink to yellow after metal ion complexation giving a yellow-pink-yellow, reversible colorimetric reaction and a “on-off-on” fluorescence in acetonitrile. The binding stoichiometry between the receptors and the anions and cations was found to be 1:1 and 2:1 respectively. The binding process was also followed by 1H NMR titrations which corroborated the previous findings.